Ginger Rhizome Fly, Mimegralla coeruleifrons (Macquart, 1844), Management by Planting Appropriate Seed Rhizome Size and Suitable Variety - Gautam, Janarjan (Journal of Agriculture and Forestry University, 2025)
A field experiment was conducted at Ginger Research Program (GRP), Salyan during 2019 and 2020 to evaluate ginger varieties (Kapurkot Aduwa-1 and Kapurkot Aduwa-2) for their seed rhizome sizes (20, 40, 60, and 80 g) on yield performance and rhizome fly, Mimegralla coeruleifrons (Macquart, 1844), management. The experiment was laid out in a Randomized Complete Block Design (RCBD) with eight treatments and three replications using 3.6 m² plots size at 30 cm × 30 cm crop geometry. Seed rhizomes were planted in late March of 2019 and 2020 and harvested after 9 months in December. Fertilization was done at the rate of 30 ton FYM and 75:50:50 kg NPK per hectare, respectively. Results demonstrated that Kapurkot Aduwa-2 variety with 80 g seed rhizomes produced the mean maximum plant height (81.6 cm), the highest tiller numbers (10.1 per clump) and the highest fresh rhizome yields (32.43 t/ha in 2019 and 28.67 t/ha in 2020). Similarly, larger seed rhizomes (60-80 g) of this variety consistently showed better resistance to rhizome fly and lower pest populations (1.47-3.33 maggots and 1.27-5.3 pupae/rhizome). Larger seed rhizomes (60-80 g) significantly reduced rhizome fly infestation and minimal damage (0.19 t/ha) in Kapurkot Aduwa-2. The study concludes that Kapurkot Aduwa-2 variety with the use of 80 g seed rhizomes provides the maximum yield and effective rhizome fly pest management, representing the most suitable cultivation strategy for ginger production in the mid-hills of Nepal. This method of production can mitigate the use of chemical pesticides to control rhizome flies and could be an avenue for the export of pesticide free ginger from Nepal to international markets.